Muscle strength and functionality of hospitalized patients admitted for respiratory affections (Research, Society and Development, 2021)
Objective: To analyze the muscle strength and functionality of hospitalized patients admitted for respiratory conditions. Methodology: Cross-sectional study, carried out in patients diagnosed and hospitalized with respiratory diseases. The assessments were performed using the Medical Research Council (MRC), Functional Independence Measure (MIF), World Health Disability Assessment Schedule (WHODAS), manovacuometry and dynamometry in patients admitted to Hospital University Student of Lagarto. Results: 97 patients participated in the respective study, where a reduction in peripheral and respiratory muscle strength was observed. When analyzing functionality, moderate functional difficulty was noted, both instruments being correlated (r= -722; p